AVALIAÇÃO ESTRATÉGICA DA PRODUTIVIDADE ACADÊMICA DE DOCENTES DE CURSOS DE GRADUAÇÃO - Marcus Vinicius Cesso; Renato Ribeiro Nogueira Ferraz (Revista Gestão Universitária na América Latina, 2019)
The Brazilian Higher Education Institutions (HEI) have their undergraduate courses evaluated periodically by the National Institute of Studies and Educational Research Anísio Teixeira (INEP). Among the criteria defined by INEP, highlight the Faculty and Tutorial dimension, which corresponds to 30% of the total grade of HEI undergraduate courses. Thus, the present study aims to use the computational tool Scriptemec for the continuous and automated evaluation of the academic production of undergraduate courses in Nursing and Medicine, from a private HEI. Applying a mixed methodology, the academic productivity criteria, such as bibliographic production, technical production, and popularization of the research results of the institution's professors were evaluated in a quantitative and qualitative approach, allowing a longitudinal analysis of the data in a long period of time. As a contribution of the present study is reinforced the possibility of studying the academic performance in undergraduate teaching research with the support of a strategic tool of free access, allowing an optimization in the analysis of indicators of intellectual productivity, besides the construction of an automated dashboard with the academic productivity data of the professors, enabling the continuous monitoring of these indicators to render accounts to the INEP and internal evaluation of the institution.